Developing a safety culture in manufacturing industry based on human behavior - Sukadarin, Ezrin Hani
With reference to the statistics by (DOSH Malaysia, 2015), accidents that caused non-permanent and permanent disabilities among workers were the highest in the manufacturing industry. Until February 2016, investigated numbers of death, non-permanent disability, and permanent disability in the manufacturing industry were 3, 324 and 13 of cases respectively (DOSH 2016). This two months statistics are alarming and elucidate the needs to conduct scientific research to find the best way to solve the problem. In 2005, a total number of 51,829 industrial accidents had been reported to the Department of Safety and Health, Malaysia. Analysis shows, there will be 6.93 accidents that involve death in 100,000 workers and 5.16 accidents in 1000 workers. However, in 2015 numbers of reporting accident had been drop to 38,753 cases with 4.84 accidents involve death in 100, 00 workers and 2.81 numbers of accidents in 1000 workers. As a country that moving forward the rate of accidents and death should be further reduced (Pelan Induk Keselamatan dan Kesihatan Pekerjaan, Kementerian Sumber Manusia Jabatan Keselamatan dan Kesihatan Pekerjaan 2016). In this study, taking at-risk behavior will be studied. It is reliable in determining the level of safety and health awareness since accidents in the manufacturing industry depend on various factors, such as the number of products being undertaken (Burton, S. 2012). Further to this, the most effective interventions employed known behavior modification principles, resulting in an intervention framework known as the behavioral safety approach (Geller 2001).